Portable constant load tensile-corrosion test system - Baharudin, B. T. Hang Tuah; Jaafar, Jamiluddin; Leman, Zulkiflle; Ismail, Napsiah (2013)
A system for performing tensile and corrosion test of a material includes a test assembly (200) for holding a specimen of the material, a load applying mechanism (250) for applying a load to the specimen of the material, and a driving system (255) coupled to the load applying mechanism (250) for controlling application of the load to the specimen of the material. Particularly, the load applying mechanism (250) is operably coupled to the test assembly (200).